Developing a comprehensive framework for evaluating public health emergency management program implementation: A scoping review - Sasie, Sileshi Demelash; Ayano, Getinet; Van Zuylen, Pien; Aragaw, Fantu Mamo; Darebo, Tadele Dana; Guerrero-Torres, Lorena; Mulugeta, Afework; Spigt, Mark (Public health (London), 2025)
Public health emergencies and disasters highlight gaps in health systems' emergency preparedness capabilities. Developing robust public health emergency management (PHEM) programs is crucial yet challenging. Existing assessment tools are limited in scope or lack standardized measurement. The aim of this study was to identify core domains of PHEM implementation status and key influencing factors. A scoping review. A literature review and focused desk review were conducted. We searched PubMed, Web of Science, Scopus, and Google Scholar to retrieve relevant studies that explored existing PHEM frameworks, core components, factors influencing implementation, and evaluation tools presented in empirical studies. Additionally, a systematic search of authoritative organizational websites was performed to identify relevant guidelines and frameworks. Subject matter experts consolidated the findings from these diverse data sources through a consultative desk review process. Out of 7232 studies identified, 50 studies met the eligibility criteria and were included in this review. Four core domains of PHEM implementation status were identified: overall implementation level; individual factors (capacity building, resources, engagement, and attitudes); organizational factors (information sharing, community involvement, planning, responsibilities, resources, leadership, monitoring/evaluation, coordination, infrastructure, and policies); and overarching factors (workforce, funding, governance, and collaboration. Nineteen key influencing factors emerged, including elements such as leadership, resource allocation, and stakeholder engagement. A conceptual framework was developed that incorporates these thematic domains from major health agencies and determinants identified through qualitative, quantitative, and mixed-methods research. This review developed a preliminary evaluation framework for PHEM programs based on a comprehensive synthesis of global evidence. The framework lays the groundwork for further validation and application to advance standardized assessments of PHEM capabilities across diverse contexts, ultimately aiming to strengthen health system resilience against emergencies.